The Effect of Work Motivation and Knowledge Sharing on Employee Performance with Job Satisfaction as a Mediating Variable : (Study at the Investment Service and One-Stop Integrated Service in Probolinggo Regency) - Maulina Yuniarti; Mursidi Mursidi; Ratya Shafira Arifiani (Jamanika (Jurnal Manajemen Bisnis dan Kewirausahaan), 2023)
This study aims to determine the effect of work motivation and knowledge sharing on employee performance with job satisfaction as a mediating variable. This research was conducted at the Investment and One Stop Service Office in Probolinggo Regency with a total of 50 respondents. The type of research used is explanatory research with a quantitative approach. The sampling technique uses non-probability sampling with saturated sample techniques. Data collection is done by distributing questionnaires. The data analysis method used is path analysis using SmartPLS 3.0 software. The results of this study are work motivation and knowledge sharing has a significant effect on employee performance, work motivation, and knowledge sharing has a significant effect on job satisfaction, meanwhile, job satisfaction has no significant effect on employee performance, work motivation has no effect significant effect on employee performance through job satisfaction, and knowledge sharing has no significant effect on employee performance through job satisfaction.